Resistenza e interpretazione - Di Bartolo, Michele (Bollettino Filosofico, 2021)
The deconstructive approach to texts is similar to psychoanalytic listening, due to its attention to apparently marginal aspects. However Derrida warns against the tendency of psychoanalysis to go beyond the signifier in the direction of the signified and tries to valorise the Freudian texts which seem to contradict this tendency. Starting with Das Unheimliche, the possibility of overcoming the semantism and hedonism that characterize previous writings emerges in Freudian discourse. The compulsion of repetition seems to name another concept of mimesis, capable of deconstructing the symbolic order. Keywords: Deconstruction, Hermeneutics, Mimesis, Psychoanalysis, Resistance